Overnight studies in severe chronic left heart failure: arrhythmias and oxygen desaturation. Issue 2 (February 1991) - Davies, S W; John, L M; Wedzicha, J A; Lipkin, D P
Abstract : Overnight studies were performed in 10 patients with severe chronic left heart failure (New York Heart Association grades III and IV) without pulmonary disease and in eight controls. Transcutaneous oxygen (Po2) and carbon dioxide tensions (Pco2) and oxygen saturation were measured and the electro-cardiogram was recorded. During sleep mean oxygen saturation fell to 92.7% (minimum 86.1%) from 95.1% when awake. During the night oxygen saturation was below 95% for 62% of the time, below 90% for 6% of the time, and below 85% for 1% of the time. In four patients there were oxygen desaturation dips (a fall of greater than 4% in oxygen saturation from a stable baseline that lasted greater than 30 s) with concurrent increases in Pco2. Two patients had bradycardia during the dips: in one there was non-sustained ventricular tachycardia during the dips and in the other there was ST depression (greater than 0.1 mV at 80 ms after the J point) during a dip. In the controls the fall in mean oxygen saturation from 95.4% when they were awake to 94.4% when they were asleep was less than the fall in patients with heart failure and there were no desaturation dips or arrhythmias. Thus patients with severe heart failure had episodes of oxygen desaturation during sleep, some of which were associated with arrhythmia. Such episodes may be related to the increased risk of sudden death in chronic heart failure.